Theorizing the (Anglican) lex orandi: A Theological Account. (14th May 2019) - Cocksworth, Ashley
Abstract: This article investigates the lex orandi, an under‐theorized yet central strand of Anglican theological identity. The aim is to provide some theological grounding to the 'law of prayer' and is motivated by the question: what, theologically speaking, does the lex orandi do? The first section explores the historical origins of the lex orandi in the Augustinian tradition and then its reception into mainstream Anglican theology. From there, the second section moves beyond Anglicanism by offering a codification of the various operations of the lex orandi, focusing in particular on its role in correcting, communicating and then complexifying Christian belief. The final section explores in further detail the nature of Christian belief as it is re‐routed through spiritual practice and takes, as a sort of test case, aspects of the doctrine of creation ex nihilo to display the 'complexifying logic' of the law of prayer.